Thermal, optical and structural properties of blocks and blends of PLA and P2HEB. Issue 3 (18th July 2018) - Makwana, Vishalkumar A; Lizundia, Erlantz; Larrañaga, Aitor; Vilas, José Luis; Shaver, Michael P
Abstract : Biodegradable diblock and triblock copolymers and blends were prepared, consisting of poly(l -lactic acid) and an aromatic/aliphatic polyester mimicking the thermal properties of polyethylene phthalate. As poly(2-(2-hydroxyethoxy)benzoate) possesses unique selective degradability and thermal properties, these novel block copolymers were explored through thermal analysis, ultraviolet–visible spectroscopy, X-ray diffraction and comparative enzymatic and catalytic degradation. Poly(l -lactic acid), the product of ring-opening polymerisation ofl -lactide by an aluminium salen catalyst, was used as a macroinitiator in the ring-opening polymerisation of 2, 3-dihydro-5 H -1, 4-benzodioxepin-5-one to obtain target diblock and triblock copolymers. Copolymerisation dramatically improved the thermal and optical properties of poly(2-(2-hydroxyethoxy)benzoate), particularly affording a copolymer with greater optical transparency whilst blocking both UV-A and UV-B light. In comparison, the polymer blends favoured non-interacting phases that worsened properties due to macro-phase separation. The chemical and enzymatic degradation profiles of the copolymers were studied by depolymerising with the aforementioned aluminium salen catalyst and degrading with proteinase K. Copolymerisation influenced the rate of chemical degradation, but retained selective degradation back to the cyclic monomer, 2, 3-dihydro-5H-1, 4-benzodioxepin-5-one.